2015
DOI: 10.1144/sjg2015-005
|View full text |Cite
|
Sign up to set email alerts
|

Sauropod dinosaur trackways in a Middle Jurassic lagoon on the Isle of Skye, Scotland

Abstract: Synopsis:The Middle Jurassic was a dynamic interval in dinosaur evolution, but the dinosaur fossil record from this time is extremely poor throughout the world. The Isle of Skye (Scotland) preserves marginal marine and terrestrial deposits of Middle Jurassic age, which have yielded sparse bones, teeth, footprints, and small segments of trackways belonging to dinosaurs. We report the discovery of the most extensive dinosaur fossil site yet known in Scotland: a coastal outcrop of the Duntulm Formation (Bathonian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 56 publications
(72 reference statements)
5
31
0
Order By: Relevance
“…A large number of eusauropod tracks were found in situ in sediments of the Duntulm Formation at Cairidh Ghulmaig at Duntulm Castle (Figure 4e) [13] and a single footprint was recorded on a loose block at Rubha nam Brathairean in rocks of the Valtos Formation [12]. Similar footprints have also been found in the Valtos Formation near Dùn Dearg in calcareous sandstones on sun cracked surfaces ( Figure 3b) [8].…”
Section: Sauropodssupporting
confidence: 55%
See 2 more Smart Citations
“…A large number of eusauropod tracks were found in situ in sediments of the Duntulm Formation at Cairidh Ghulmaig at Duntulm Castle (Figure 4e) [13] and a single footprint was recorded on a loose block at Rubha nam Brathairean in rocks of the Valtos Formation [12]. Similar footprints have also been found in the Valtos Formation near Dùn Dearg in calcareous sandstones on sun cracked surfaces ( Figure 3b) [8].…”
Section: Sauropodssupporting
confidence: 55%
“…Middle Jurassic dinosaurs are becoming better known from Scotland as more discoveries are made each year along the rocky shoreline of the Isle of Skye [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Studies of the track diversity from the Isle of Skye have shown that there are several different forms of tridactyl prints of varying sizes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The marine reptile fauna has also generated a lot of interest with research being carried out more recently by the inter-institutional collaborative group: PalAlba (Clark et al 1993, Rees & Underwood 2005, Brusatte et al 2015b.…”
mentioning
confidence: 99%
“…A scenario depicting the overall environment was presented by Hudson & Trewin (2003). Dinosaur fossils, most notably the trackways of large sauropods, are now known from the lower part of the formation (Brusatte et al 2016), northeast of where NMS G.2016.21.1 was collected.…”
Section: Systematic Palaeontologymentioning
confidence: 99%